Kinetic evaluation study on the bioactivity of silver doped hydroxyapatite‐polyvinyl alcohol nanocomposites. Issue 12 (21st March 2014) - Mostafa, Amany A.; Oudadesse, Hassane; El Sayed, Mayyada M. H.; Kamal, Gehan; Kamel, Mohamed; Foad, Enas
Abstract This work investigates the effect of adding silver nanoparticles (NPs) in ppm on the bioactivity of hydroxyapatite/polyvinyl alcohol nanocomposites (HAV). HAV prepared by an in situ biomimetic approach was doped with different concentrations of silver NPs (HAV‐Ag), and the formed powder samples were characterized by different techniques such as Inductively Coupled Plasma‐Optical Emission Spectroscopy (ICP‐EOS), X‐ray diffraction, transmission electron microscope, and Fourier Transform Infrared Spectroscopy. Bioactivity was evaluated in simulated body fluid through studying the kinetics of Ca and P uptake onto the different HAV‐Ag nanocomposites. Uptake profiles of Ca and P were well described by a pseudo‐second order kinetic model, and the obtained kinetic parameters confirmed that the highest uptake capacities were achieved by adding less than 0.001 ppm of silver NPs which is an amount not detectable by ICP. Furthermore, HAV‐Ag nanocomposites were shown to be non‐toxic as well as have a strong antibacterial effect. Silver NPs significantly enhanced the bioactivity of HAV nanocomposites and thus the developed nanocomposites promise to be excellent biomaterials for bone and reconstructive surgery applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4609–4615, 2014.